Nogo‐B promotes tumor angiogenesis and provides a potential therapeutic target in hepatocellular carcinoma. Issue 12 (26th October 2018) - Cai, Hao; Saiyin, Hexige; Liu, Xing; Han, Dingding; Ji, Guoqing; Qin, Bo; Zuo, Jie; Shen, Suqin; Yu, Wenbo; Wu, Jiaxue; Wu, Yanhua; Yu, Long
Abstract : Tumor angiogenesis is one of the hallmarks of cancer as well as an attractive target for cancer therapy. Characterization of novel pathways that act in parallel with the VEGF/VEGFR axis to promote tumor angiogenesis may provide insights into novel anti‐angiogenic therapeutic targets. We found that the expression level of Nogo‐B is positively correlated with tumor vessel density in hepatocellular carcinoma (HCC). While Nogo‐B depletion inhibited tumor angiogenesis, Nogo‐B overexpression promoted tumor angiogenesis in a tumor xenograft subcutaneous model of the human HCC cell line. Mechanically, Nogo‐B regulates tumor angiogenesis based on its association with integrin αv β3 and activation of focal adhesion kinase. Moreover, Nogo‐B antibody successfully abolished the function of Nogo‐B in tumor angiogenesis in vitro and in vivo . Collectively, our results strongly suggest that Nogo‐B is an important tumor angiogenic factor and blocking Nogo‐B selectively inhibits tumor angiogenesis. Abstract : We found that the expression level of Nogo‐B is positively correlated with tumor vessel density in hepatocellular carcinoma and promotes tumor angiogenesis in vitro and in vivo, while Nogo‐B antibody inhibited tumor angiogenesis in vitro and in vivo . Collectively, our results strongly suggest that Nogo‐B is an important tumor angiogenic factor and blocking Nogo‐B selectively inhibits tumor angiogenesis.